The association between hobby engagement and depressive symptoms among Chinese middle-aged and older adults: evidence from the China health and retirement longitudinal study - Lu, Qiong; Hu, Peijing; Lian, Cheng; Chen, Xinglin (Frontiers in Public Health, 2024)
BACKGROUND: It has been demonstrated that receptive cultural engagement, such as visits to theatres and museums, can reduce depression in older adults. However, the association between hobby engagement and lower rates of depressive symptoms (DS) remains unclear. The objective of this study was to investigate the potential relationship between hobby engagement and depressive symptoms.The data for this prospective cross-sectional study were collected from participants in the China Longitudinal Study of Health and Retirement (CHARLS) wave 2020. To assess DS, a score of 10 or more on the Center for Epidemiological Studies Depression Scale was used to indicate depression. Hobby engagement was gauged by trained staff through the administration of a battery of standardised questions. Logistic regression and inverse probability of treatment weighting (IPTW) using the propensity score analyses were employed to investigate the relationship between hobby engagement and DS. RESULTS: A total of 16,057 participants were included, with a mean age of 62.4±9.2 years. Of these, 7699 were male and 8358 were female. The proportion of individuals exhibiting depressive symptoms was 31.57% (1286 out of 4073) among those with hobby engagement, while it was 39.67% (4754 out of 11984) among those without hobby engagement. After adjusting for covariates, the odds ratio was 0.89 (95% CI: 0.82-0.97, P = 0.0109). Propensity-score analyses also supported these findings, with the odds ratio being 0.91 (95% CI: 0.84-0.99, P = 0.0204). The finding was consistent with multiple sensitivity analyses. CONCLUSIONS: Our study found hobby engagement was associated with a reduced risk of depressive symptoms in Chinese middle-aged and older adults. Our findings need to be confirmed in future studies.